4(x-6)=4x-6

Simple and best practice solution for 4(x-6)=4x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-6)=4x-6 equation:


Simplifying
4(x + -6) = 4x + -6

Reorder the terms:
4(-6 + x) = 4x + -6
(-6 * 4 + x * 4) = 4x + -6
(-24 + 4x) = 4x + -6

Reorder the terms:
-24 + 4x = -6 + 4x

Add '-4x' to each side of the equation.
-24 + 4x + -4x = -6 + 4x + -4x

Combine like terms: 4x + -4x = 0
-24 + 0 = -6 + 4x + -4x
-24 = -6 + 4x + -4x

Combine like terms: 4x + -4x = 0
-24 = -6 + 0
-24 = -6

Solving
-24 = -6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -5(0.2x+0.1)-0.6=1.9 | | 8(2x+5)=7(x+3)+11 | | 2x-4=3x+14 | | 5n^2+19-68=-2 | | 24=-4(3x-6) | | 20x^2+124x+24= | | 6x+18=3x | | 9+12c+4c^2=0 | | x^2+7x-45=0 | | X^2+14x+35=-5 | | 3p-12=6+p | | y=34.3(105)-2524 | | 2y-2=19+2h | | (4y+11)=(3y^2-2y-7) | | -7=7(-6+3x)-7(4x-5) | | -x^2+20x-51=0 | | x+2.5x+3x=27 | | 7x+152=3x+124 | | y-563=34.3(-90) | | x^6-4x^5-21x^4=0 | | 2.6+3.2e=-23 | | 7x+152=3x+121 | | -7(6+3v)=105 | | 9.2m-6.3=-36.3+4.2m | | 8y-20=32 | | 60+27t+3t^2=0 | | 9x-95=5x-23 | | 10(a-4)=-5 | | 2(x-2)=2/5(3x+1)+2 | | -4(3y-8)-y=-3 | | 8x+63=5x+21 | | 6=x+2/3 |

Equations solver categories